2022
DOI: 10.30892/gtg.40104-800
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of a New Religious Travel Segment: Umrah Do It Yourself Travellers (Diy)

Abstract: This research examines the rise of a new religious travel segment – the Umrah Do It Yourself (DIY) travellers. While Hajj is the fifth pillar of Islam, Umrah is a minor Muslim pilgrimage that can be undertaken at any time of the year, while still playing a crucial role in the completion of Hajj rituals. In the past, Umrah was managed by an authorised travel agent, who makes all the necessary pilgrimage preparations, from flights to trip itineraries. Recent years have seen an upsurge in travellers who prefer no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…However, the pilgrimage to Mecca takes two forms: Hajj and Umrah. The Hajj takes place in the last month of the Islamic calendar, and it is obligatory for every Muslim once in life, whereas the Umrah is performed at any time of the year [ 19 , 20 ]. During the visit to Mecca, Muslims pray in the Grand Mosque (Masjid al-Haram) and visit religious sites such as Safa and Marwa Mountain in order to pray, find peace, happiness and follow Prophet Muhammed (PBUH) on his last visit to Mecca [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the pilgrimage to Mecca takes two forms: Hajj and Umrah. The Hajj takes place in the last month of the Islamic calendar, and it is obligatory for every Muslim once in life, whereas the Umrah is performed at any time of the year [ 19 , 20 ]. During the visit to Mecca, Muslims pray in the Grand Mosque (Masjid al-Haram) and visit religious sites such as Safa and Marwa Mountain in order to pray, find peace, happiness and follow Prophet Muhammed (PBUH) on his last visit to Mecca [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The other main area of research is the study of the spatial distribution of religious institutions, with particular attention paid to the geographical features of the settlements and focusing on the most important buildings used for religious purposes (churches, mosques, synagogues). Studies on the spatial structure of medieval towns have shown that these buildings, and in larger towns the central units (Christian religion-cathedral, Islamic religion-central mosque), were predominantly located in the central parts of the settlements, in order to meet the need for easy accessibility (Atikah et al 2022;Bitušíková 2022;Hronček et al 2022;Neumannová 2022;Sági 2022;Sjoberg 1955); this was observed both in the case of Christian churches (e.g., Nicholas 2003;Ballard 2005) and Islamic mosques (Ehlers and Floor 1993;Kheirabadi 2000). Furthermore, however, it has also been highlighted that smaller sub-centres were established in larger cities, of which church complexes constituted a substantial part (Gutiérrez 2015;Burtenshaw et al 2021).…”
Section: Introductionmentioning
confidence: 99%